AVALIAÇÃO LABORATORIAL E MONITORAÇÃO DA PRESSÃO INTRACRANIANA ATRAVÉS DE UM MÉTODO INOVADOR NÃO INVASIVO EM GESTANTES - Silveira, Daniel da (2016)
Intracranial hypertension causes several complications when installed, it can severely affect the individual afflicted with permanent sequelae, besides the risk of death. In the case of pregnant women, the risk is even greater due to the high complexity involved in physiological pregnancy period. In this context, the evaluation of intracranial pressure (ICP) could provide important information that can detect these problems and thereby prevent these complications. However, the invasive method that this procedure is performed makes the use of this methodology very limited. It’s necessary the use of a method that is capable of generating this information while providing security to the patient, not generating complications such as infections or injuries resulting from its invasive form. The aim of this study was to evaluate a new technology for noninvasively ICP measuring in pregnant women in a municipal health center in Ponta Grossa, relating it to the clinical and laboratory data obtained at the time of the procedure. It was observed that low and high-risk pregnant women showed a high in ICP. There were also significant differences between groups for laboratory parameters, such as serum levels of alkaline phosphatase and ultra-sensitive C-reactive protein (hs-CRP). The existence of changes in the ICP and its relationship with clinical and laboratory data in the population studied, introduces in the monitoring of pregnant women, a parameter with unknown data due to technical limitations, which allows to identify changes even in the absence of symptoms and to prevent complications related to elevation in intracranial pressure.